Get the answers you need at Westonci.ca, where our expert community is always ready to help with accurate information. Discover the answers you need from a community of experts ready to help you with their knowledge and experience in various fields. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the equation given in the hint, we need to find the value of [tex]\( r \)[/tex] for which the equation holds true. We start with the combinatorial notation and the given hint. The given equation is:
[tex]\[ 12 \cdot {^r}C_2 = {^{r+2}}C_3 \][/tex]
We know the general formula for combinations, where [tex]\({^n}C_k = \frac{n!}{k!(n-k)!} \)[/tex]. Applying this formula, we get:
[tex]\[ {^r}C_2 = \frac{r!}{2!(r-2)!} = \frac{r(r-1)}{2 \times 1} = \frac{r(r-1)}{2} \][/tex]
[tex]\[ {^{r+2}}C_3 = \frac{(r+2)!}{3!(r-3)!} = \frac{(r+2)(r+1)r}{3 \times 2 \times 1} = \frac{(r+2)(r+1)r}{6} \][/tex]
Plugging these back into the given equation:
[tex]\[ 12 \cdot \frac{r(r-1)}{2} = \frac{(r+2)(r+1)r}{6} \][/tex]
Now simplify each side:
[tex]\[ 12 \cdot \frac{r(r-1)}{2} = 6r(r-1) \][/tex]
So, the equation becomes:
[tex]\[ 6r(r-1) = \frac{(r+2)(r+1)r}{6} \][/tex]
Multiplying both sides by 6 to clear the fraction, we get:
[tex]\[ 36r(r-1) = (r+2)(r+1)r \][/tex]
Dividing both sides by [tex]\( r \)[/tex] (assuming [tex]\( r \neq 0 \)[/tex]):
[tex]\[ 36(r-1) = (r+2)(r+1) \][/tex]
Expanding the right side:
[tex]\[ 36(r-1) = r^2 + 3r + 2 \][/tex]
Distribute and simplify the left side:
[tex]\[ 36r - 36 = r^2 + 3r + 2 \][/tex]
Bringing all terms to one side to set the equation to zero:
[tex]\[ r^2 + 3r + 2 - 36r + 36 = 0 \][/tex]
[tex]\[ r^2 - 33r + 38 = 0 \][/tex]
Now, we solve this quadratic equation using the quadratic formula [tex]\( r = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1, b = -33, \)[/tex] and [tex]\( c = 38 \)[/tex]:
[tex]\[ r = \frac{33 \pm \sqrt{(-33)^2 - 4 \cdot 1 \cdot 38}}{2 \cdot 1} \][/tex]
[tex]\[ r = \frac{33 \pm \sqrt{1089 - 152}}{2} \][/tex]
[tex]\[ r = \frac{33 \pm \sqrt{937}}{2} \][/tex]
Thus, the solutions are:
[tex]\[ r = \frac{33 - \sqrt{937}}{2} \quad \text{or} \quad r = \frac{33 + \sqrt{937}}{2} \][/tex]
And considering the possibility of [tex]\( r = 0 \)[/tex]:
[tex]\[ r = 0, \quad \frac{33 - \sqrt{937}}{2}, \quad \frac{33 + \sqrt{937}}{2} \][/tex]
These are the solutions for the given equation.
[tex]\[ 12 \cdot {^r}C_2 = {^{r+2}}C_3 \][/tex]
We know the general formula for combinations, where [tex]\({^n}C_k = \frac{n!}{k!(n-k)!} \)[/tex]. Applying this formula, we get:
[tex]\[ {^r}C_2 = \frac{r!}{2!(r-2)!} = \frac{r(r-1)}{2 \times 1} = \frac{r(r-1)}{2} \][/tex]
[tex]\[ {^{r+2}}C_3 = \frac{(r+2)!}{3!(r-3)!} = \frac{(r+2)(r+1)r}{3 \times 2 \times 1} = \frac{(r+2)(r+1)r}{6} \][/tex]
Plugging these back into the given equation:
[tex]\[ 12 \cdot \frac{r(r-1)}{2} = \frac{(r+2)(r+1)r}{6} \][/tex]
Now simplify each side:
[tex]\[ 12 \cdot \frac{r(r-1)}{2} = 6r(r-1) \][/tex]
So, the equation becomes:
[tex]\[ 6r(r-1) = \frac{(r+2)(r+1)r}{6} \][/tex]
Multiplying both sides by 6 to clear the fraction, we get:
[tex]\[ 36r(r-1) = (r+2)(r+1)r \][/tex]
Dividing both sides by [tex]\( r \)[/tex] (assuming [tex]\( r \neq 0 \)[/tex]):
[tex]\[ 36(r-1) = (r+2)(r+1) \][/tex]
Expanding the right side:
[tex]\[ 36(r-1) = r^2 + 3r + 2 \][/tex]
Distribute and simplify the left side:
[tex]\[ 36r - 36 = r^2 + 3r + 2 \][/tex]
Bringing all terms to one side to set the equation to zero:
[tex]\[ r^2 + 3r + 2 - 36r + 36 = 0 \][/tex]
[tex]\[ r^2 - 33r + 38 = 0 \][/tex]
Now, we solve this quadratic equation using the quadratic formula [tex]\( r = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \)[/tex], where [tex]\( a = 1, b = -33, \)[/tex] and [tex]\( c = 38 \)[/tex]:
[tex]\[ r = \frac{33 \pm \sqrt{(-33)^2 - 4 \cdot 1 \cdot 38}}{2 \cdot 1} \][/tex]
[tex]\[ r = \frac{33 \pm \sqrt{1089 - 152}}{2} \][/tex]
[tex]\[ r = \frac{33 \pm \sqrt{937}}{2} \][/tex]
Thus, the solutions are:
[tex]\[ r = \frac{33 - \sqrt{937}}{2} \quad \text{or} \quad r = \frac{33 + \sqrt{937}}{2} \][/tex]
And considering the possibility of [tex]\( r = 0 \)[/tex]:
[tex]\[ r = 0, \quad \frac{33 - \sqrt{937}}{2}, \quad \frac{33 + \sqrt{937}}{2} \][/tex]
These are the solutions for the given equation.
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.